First record of the myxomycete genus Colloderma in Central America - Rojas Alvarado, Carlos Alonso (2015)
The myxomycete genus Colloderma and the species Colloderma oculatum are reported for the first time in Central America. The species was recorded at high elevations in the Talamanca Mountain Range in Costa Rica during 2014 in a location where the structure of myxomycete assemblages has been historically associated with temperate rather than tropical communities. Comments on the geographical distribution and ecology of the species are included. This record has increased the number of Costa Rican myxomycetes to 213 according to the most updated checklist.